DESIGNING A TRANSITION SYSTEM TO PERSONALIZED LEARINING: ANALYSIS OF THE RESULTS OF THE STAKEHOLDER SURVEY - Seitahmetova, Zhanat; Kumargazhanova, Saule; Bobrov, L. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The issue of the transition of schools in Kazakhstan to a personalized format of education using information technology in the context of a global pandemic is relevant and requires careful study. This study aims to identify the factors that contribute to the effective implementation of personalized learning in specialized schools for gifted students. As a method, we chose a real-time survey of stakeholders within the framework of a logical-structured approach. Data processing was carried out using the MS Forms software application. The surveys were aimed at obtaining the views of students, parents and teachers to confirm the real problems of introducing personalized learning in schools. The results of the study made it possible to identify the main five factors contributing to the implementation of software in the educational process of schools and can be taken into account in the process of developing a design system for the transition to personalized learning.